Prostate cancer morbidity in the Mari El Republic: A retrospective observational study - D. V. Pasynkov; R. I. Fatykhov (Кубанский научный медицинский вестник)
Background. Prostate cancer maintains a relatively high standardized uptake value and share of patients followed up for 5 or more years. Accordingly, distant outcomes in these patients appear to be influenced by factors other than the underlying disease.Objective. To analyze the morbidity in prostate cancer patients with additional malignancies potentially linked with the decrease in the survival rate in the Mari El Republic.Methods. The present study involved 1434 prostate cancer patients firstly enrolled in the period from 2012 to 2021. A group of patients in this sample was identified with additional malignancies (other than prostate cancer) diagnosed within the period from 6 months prior to prostate cancer diagnosis to the end of 2021. Comparison of the incidence of malignancies among prostate cancer patients and the general population was performed via a 2 × 2 crosstab analysis by calculating the relative risk and its 95% confidence interval. The difference was considered significant when 95% confidence interval did not include 1. In addition, chi-square values and corresponding p-values were calculated. Statistical analyses were performed using SPSS 13.0 (SPSS Inc., USA) and Microsoft Excel 2007 (Microsoft Corporation, USA).Results. 31 (32.29%) additional malignancies were identified (prostate cancer was diagnosed within 6 months before prostate cancer diagnosis and up to 6 months thereafter), 7 additional malignancies (7.29%) were registered 6 months to 1 year after prostate cancer diagnosis, and 61 additional malignancies (63.54%) during the later period. The most common primary malignancies among all patients included: bladder cancer (relative risk = 15.23 [95% confidence interval: 10.42–22.26]), nonmelanoma skin cancer (relative risk = 3.77 [2.34–6.07]), colorectal cancer (relative risk = 2.10 [1.24–3.54]), gastric cancer (relative risk = 2.01 [1.08–3.73]), and kidney cancer (relative risk = 4.69 [2.51–8.75]).Conclusion. Within 7.1 years (median) of follow-up, additional malignancies develop in 6.70% of prostate cancer patients. These patients reveal the higher risk than the population average value, thereby constituting a risk group.